On Commutativity and Centralizers of Prime Ring with Involution: Adnan Abbasi, Mohd Shadab Khan, Muzibur Rahman Mozumder - Team, Support (Thai Journal of Mathematics, 2022)
The main purpose of this paper is to study the commutativity of prime rings with involution satisfying certain *-identities involving left centralizers.